Understanding Online Reading Dispositions from the Perspective of Saudi EFL Learners - Yaghi, Eyhab; Abdullah, Amelia (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Our knowledge of online reading dispositions is based on limited data. The optimal aim of this paper is to find out the online reading disposition that might take place when EFL students read online materials. To achieve the aim of this research, a mixed method approach was employed. The results emerged from the quantitative data have shown that students tend to show dispositions of reflection as the most frequent dispositions. In compliance with quantitative data, five students were interviewed in order to provide a deep understanding of these dispositions. By doing so, new ideas have been extracted from students’ responses such as likeness toward online reading, taking place online reading dispositions and alternatives of online reading dispositions. These emerging results would provide an overwhelming idea about the online reading dispositions and pave the way for upcoming studies.